2022
DOI: 10.33588/rn.7503.2022173
|View full text |Cite
|
Sign up to set email alerts
|

Efectos del sobrepeso y la obesidad en las funciones cognitivas de niños y adolescentes

Abstract: Introducción. Investigaciones recientes sugieren que el sobrepeso y la obesidad en niños y adolescentes afectan a los procesos cognitivos y pueden alterar el aprendizaje escolar. En particular, las denominadas funciones ejecutivas, como la capacidad de inhibición de la respuesta, el control de la impulsividad, la flexibilidad cognitiva, la planificación y la toma de decisiones, se han relacionado de forma inversa con el índice de masa corporal. Objetivo. Este trabajo pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…With the increased prevalence of obesity and the earlier onset of obesity in the population, there may be a significant rise in the incidence and prevalence of Alzheimer’s disease among younger individuals [ 15 ]. Childhood obesity, which is highly prevalent, has been linked to various health issues, including cognitive impairment during childhood [ 16 , 17 ]. Longitudinal studies examining the association between childhood obesity and cognitive function in midlife have revealed that childhood obesity has a detrimental effect on cognition later in life [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the increased prevalence of obesity and the earlier onset of obesity in the population, there may be a significant rise in the incidence and prevalence of Alzheimer’s disease among younger individuals [ 15 ]. Childhood obesity, which is highly prevalent, has been linked to various health issues, including cognitive impairment during childhood [ 16 , 17 ]. Longitudinal studies examining the association between childhood obesity and cognitive function in midlife have revealed that childhood obesity has a detrimental effect on cognition later in life [ 18 ].…”
Section: Introductionmentioning
confidence: 99%